БИЛИМЛЕНДИРИЎДИҢ ҮЗЛИКСИЗЛИГИН ТӘМИЙИНЛЕЎ – ТӘЛИМ - ТӘРБИЯНЫҢ БЕККЕМ ТАЯНЫШЫ - Шразов, М. (SCIENCE and SOCIETY, 2021)
The article discusses the importance of the 11-year education system in the secondary schools of country. It is said that in the process of continuing education, the teaching of school-age children is much improved.